Local government in the local economy - Hajduga, Piotr; Łuczyszyn, Andrzej (Samorząd terytorialny w gospodarce lokalnej, 2019)
Today, local government must not only create the appropriate conditions and climate for the implementation of the tasks imposed on it, but must also be an economic entity actively participating in managing the local economy. In light of analyses of the average local government’s scope of activities, it is clear that there is an increasing lack of complementarity in strategic decisions, and growing disparities or errors of local authorities, which become barriers to local development. This fact often leads to economic and social stagnation. Frequently the effectiveness of local government structures does not go hand in hand with economic rationality, which attracts social criticism. Under these conditions, the role of local government should change in local economy management with a focus on, among others, creative capital, whose task will be to expand the impact of the local economy on other areas. In addition, local government makes the local development policy more flexible, in particular the social policy towards strengthening local communities
Biblioteka Regionalisty, 2019, Nr 19, s. 66-75
Keywords: Dolny Śląsk